STUDY OF OPTIMUM CONDITIONS IN DETECTION OF ABO GENOTYPE BY SIMULTANEOUS PCR-RFLP METHOD - Mohammed, Ahmed; Omar, Ammirah; Nader, Mohammed (Iraqi Journal of Science, 2024)
Extracted of DNA from blood samples, and amplification two separate segments of the glycosyl transferases gene containing nucleotide 261 in exon 6 and nucleotide 703 in exon 7 of ABO gene locus were amplified . ABO locus gene was amplified by using two sets of specific primers for ABO locus as a whole. The first set includes the primer pair (1 and 2) that was used for the amplification of 200 bp DNA fragment, which contains the nucleotide 261. The second set includes the primer pair (3 and 4) that was used to amplify a 128 bp DNA fragment, which contains the nucleotide703. Nucleotides 261 and 703 were used to distinguish A , B, O alleles by restriction enzyme digestion of the PCR products. The amplified DNA products were then run on 2% agarose gel .Two types of restriction enzyme were used. The first was KpnI which determined the deletion at nucleotide 261(G→ - ) of O allele, while the second one was AluI which determined the substitution in nucleotide 703 ( G → A ) that detect B allele which can be recognized from A allele (AluI digest the DNA of individual with type B allele). Digested DNA fragments were run on 6% low melting agarose. The thirty samples show 14 ( A )blood group, 13 of them are Heterozygous AO and one is Homozygous AA . The 14 samples are blood group B, 13 of them are Heterozygous BO and one of them is Homozygous BB. One sample for AB, O blood groups this type have only Homozygous phase and each gene are dominant in AB type so called co-dominant. In O type the gene is recessive and expressed only in Homozygous type only whereas the A and B genes are dominant over O.